Legal and regulatory implications of Artificial Intelligence (AI) (Publications Office of the European Union, 2019)
AI will have numerous positive impacts on various aspects of our daily life, but it also presents several challenges. To fully benefit from AI potential, an appropriate regulatory and enabling framework needs to be put in place. This report presents the findings of a EIT/JRC joint project seeking to identify legal and regulatory challenges the usage of AI technology may bring for start-ups, in an attempt to raise awareness and knowledge about potential hurdles. The report contains the summary of the Workshop
10.2760/527052
Keywords: Amtsdruckschrift; Graue Literatur; Künstliche Intelligenz; Regulierung; E-Health; Autonomes Fahrzeug; Data Mining; EU-Staaten; artificial intelligence; e-Health; intelligent transport system; legislation; data processing; intellectual property; product safety; producer's liability; civil liability; digital technology; new technology; medical device; document retrieval; autonomous vehicle; research report